Análise de geração para caracteres de porte e qualidade de fruto em pimenteiras ornamentais (Capsicum annuum L.). - Fortunato, Flávia Laís Gomes (2018)
Peppers are grown all over the world, and their agribusiness has been gaining greater market share because of the wide variety of products, uses, and forms of consumption. The cultivation of ornamental peppers is a new trend in the Brazilian consumer market and has been increasing gradually throughout the world. The genetic variability existing in the genus Capsicum is basic conditions for their use in breeding programs. Knowledge of gene interaction and inheritance is essential for the definition of efficient breeding strategies. In this way, this study aimed to estimate the genetic parameters and gene effects involved in the inheritance of size, flower, and fruit characters in segregating generations of ornamental pepper (Capsicum annuum L.). The experiment was carried out in a greenhouse at the Plant Biotechnology Laboratory, Federal University of Paraíba (UFPB), Areia - PB. In the first chapter, two accessions of ornamental pepper (Capsicum annuum L.) belonging to the germplasm bank of the Federal University of Paraíba (BGH-UFPB) were used as parents: UFPB 347 and UFPB 356. In the second chapter the accesses UFPB 349 and UFPB 356 were used as parents. These parental were crossed to obtain the F1 generation, this turn, was self- fertilized to obtain generation F2. The backcrossing generations RC1 and RC2 were obtained through the crossing between F1 and the parental P1 and P2, respectively. The experimental design was completely randomized, with five plants of each parental (P1 and P2), 20 plants of the F1 generation, 90 plants of the generation F2 for crossing 347 x 356, and 88 plants for the crossing 349 x 356, and 40 plants of RC1 and RC2. We evaluated 19 quantitative characters referring to the plant, flower and fruit. The obtained data were submitted to generation analysis, and the effects of the models were submitted to the t test at the 5% and 1% level of significance. For generation analysis involving parental 347 and 356 high heritability values in the broad sense were observed for corolla length, petal diameter, fruit weight, fruit length and pericarp thickness. However, only the corolla length showed high heritability of restricted sense. The additive-dominant model (m, a, d) was adequate to explain the genetic parameters of most of the characteristics evaluated, except for anther length and dry matter content, in which the additive-dominant model was inadequate, being interpreted the complete model. In the generation analysis involving parentheses 349 and 356, only plant height and pericarp thickness showed high heritability in the broad and restricted sense. The additive-dominant model (m, a, d) was adequate to explain the genetic parameters of most characteristics. However, for the canopy diameter, petal diameter, pedicel length and dry matter content, the additive-dominant model was inadequate and the interpretation of the complete model was recommended.